Immediate and persistent transcriptional correlates of long-term sensitization training at different CNS loci in Aplysia californica. - Samantha Herdegen; Catherine Conte; Saman Kamal; Robert J Calin-Jageman; Irina E Calin-Jageman (PLoS ONE, 2014)
Repeated noxious stimulation produces long-term sensitization of defensive withdrawal reflexes in Aplysia californica, a form of long-term memory that requires changes in both transcription and translation. Previous work has identified 10 transcripts which are rapidly up-regulated after long-term sensitization training in the pleural ganglia. Here we use quantitative PCR to begin examining how these transcriptional changes are expressed in different CNS loci related to defensive withdrawal reflexes at 1 and 24 hours after long-term sensitization training. Specifically, we sample from a) the sensory wedge of the pleural ganglia, which exclusively contains the VC nociceptor cell bodies that help mediate input to defensive withdrawal circuits, b) the remaining pleural ganglia, which contain withdrawal interneurons, and c) the pedal ganglia, which contain many motor neurons. Results from the VC cluster show different temporal patterns of regulation: 1) rapid but transient up-regulation of Aplysia homologs of C/EBP, C/EBPγ, and CREB1, 2) delayed but sustained up-regulation of BiP, Tolloid/BMP-1, and sensorin, 3) rapid and sustained up-regulation of Egr, GlyT2, VPS36, and an uncharacterized protein (LOC101862095), and 4) an unexpected lack of regulation of Aplysia homologs of calmodulin (CaM) and reductase-related protein (RRP). Changes in the remaining pleural ganglia mirror those found in the VC cluster at 1 hour but with an attenuated level of regulation. Because these samples had almost no expression of the VC-specific transcript sensorin, our data suggests that sensitization training likely induces transcriptional changes in either defensive withdrawal interneurons or neurons unrelated to defensive withdrawal. In the pedal ganglia, we observed only a rapid but transient increase in Egr expression, indicating that long-term sensitization training is likely to induce transcriptional changes in motor neurons but raising the possibility of different transcriptional endpoints in this cell type.